Energy Wood Potential, Supply Systems and Costs in Tihvin and Boksitogorsk Districts of the Leningrad Region - Ilavský, Ján; Goltsev, Vadim; Karjalainen, Timo; Gerasimov, Yuri; Tahvanainen, Timo (Finnish Forest Research Institute, 2007)
Possibilities for energy wood procurement and use in the Leningrad region of Northwest Russia as a tool for reducing greenhouse gas emissions have been analysed in this report. Calculations have been made for selected area, where resources are available and also other preconditions are appropriate for their use for energy production. The study includes estimation of how much wood for energy purposes could be available in the vicinity of the selected area, what are suitable supply systems to consumers and what could be expected costs of energy wood procurement, when taking into account local technical and economical preconditions and constraints. Former Boksitogorsky, Tihvinsky and Sugozersky leshoses in the Tihvin and Boksitogorsk administrative districts have been selected for analysis. There are possibilities for intensification of forest resources utilisation in the region, as annual allowable cut and intermediate fellings are not fully used. Actual available volume of energy wood generated by fellings in the region is 424,000 m³ yr> . Full utilisation of annual allowable cut would increase volume of available energy wood up to 637,000 m³ yr -1 or + 50%. If also intermediate fellings are entirely utilised, available volume of energy wood could be increased up to 774,000 m³ yr -1 or + 83% to actual available volume. Productivity and costs of cut-to-lenth, tree length, full tree and tree section harvesting methods in the 1st and 2nd commercial thinnings and in final fellings with the transport of energy wood up to 100 km were analysed. The supply systems based on manual felling in thinnings have lower costs of energy wood compared to the supply systems which utilise harvesters. Utilisation of harvesters becomes more feasible for final felling, where high productivity allows the cut-to-length method to be more efficient compared to the full tree and tree length methods with manual felling. Costs of energy wood harvesting per energy unit are competitive with the price of electricity and light oil as primary ...